Ostracodes da Formação Solimões, Neógeno do estado do Amazonas, Brasil: taxonomia, paleoecologia e bioestratigrafia - PEREIRA, Ana Paula Linhares (Universidade Federal do Pará, 2019)
The analysis of 123 samples from 1AS-31-AM and 1AS-34-AM cores from the southwest of Amazonas State, Brazil allowed to recognize the abundance and diversity of ostracodes with register of five families: Cytherideidae, Limnocytheridae, Cyclocyprididae, Darwinulidae and Candonidae, distributed in six genera (Candona, Cypria, Cytheridella, Darwinula, Perissocytheridea e Cyprideis) and 23 species, 15 of them previously recorded to adjacent areas. The family Cytherideidae is the most representative with two genera and 19 species. The Cyprideis genera, as recorded in previous studies, is the most abundant representing 96% of ostracofauna and most diverse with 18 species. The ostracod stratigraphic distribution and the associated microfauna allowed the reconstruction the paleoenviromental evolution, The paleoenvironmental interpretation reveal an evolution of the depositional system in the Amazonia, which grades from continental (lacustrine) environments, at the base to a sporadically marine influenced settings into fluvial conditions at the top of the core sequence. This vertical variation might be better observed in 1AS-31-AM core. Probably, the radiation of Cyprideis is associated with sudden changes (mainly related to salinity change), supported by the presence of nodules in its shell. The biostratigraphic distribution of the Cyprideis species possibilited the determination of three biozones (OS1, OS2 e OS3), aged between the later Early Miocene/earlier Middle Miocene to later Middle Miocene/early Late Miocene. In the 1AS-34-AM core the analyzed range possibly corresponds to Middle Miocene/Late Miocene. The short-lived marine ingression reached the central part of Amazonia, probably in the Early-Middle Miocene based on the biostratigraphic model proposed here and supported by ostracod, palinological and mollusk biozonations.